Pancasila sebagai Jiwa Persatuan dalam Membangun Moderasi Beragama di Indonesia - Dominikus Doni Ola; Megawati Naibaho (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Pancasila is a legacy of our ancestors and has very noble values. Nobility is contained in the five principles of Pancasila as a noble